MORPHOLOGICAL AND BIOLOGICAL QUALITY OF Pinus radiata D. Don, MYCORRHIZED WITH Scleroderma verrucosum (Vaill) Pers. AND Rhizopogon luteolus Fr. & Nordh. IN GREENHOUSE CONDITIONS - Rodríguez-Carrillo, Marco (2021)
The effect of Scleroderma verrucosum (Vaill) Pers and Rhizopogon luteolus Fr. & Nordh. was evaluated on the morphological and biological quality of Pinus radiata D. Don plants in a nursery in Vilcashuaman, Ayacucho, Peru. Treatments: (1) Mycorrhization with Scleroderma verrucosum, (2) Mycorrhization with Rhizopogon luteolus, (3) Mixture of both fungi, and (4) Control, in a completely randomized design with 10 repetitions per treatment. The fungi came from local Pinus radiata and Eucalyptus globulus forests. The inoculation was carried out in the peal at 30 days of sowing and the evaluation at 7.5 months after the peal. The mycorrhizal pines outperformed the control with significant differences in all the variables evaluated. In the stem neck diameter and dry matter of the aerial part, the inoculated treatments did not present significant differences; however, in the height, dry matter of the root, and total dry matter, the Mixture treatment stood out. In the biological quality, a greater number of mycorrhizae was observed in the inoculated, with significant differences compared to the control without mycorrhizae. A higher percentage of monopodial mycorrhizae (91%) was evidenced in relation to dichotomous (8.5%) and coralloid (0.6%) types. Significant positive relationships were determined between the morphological variables, but these on P. radiata presented non-significant associations with the number of mycorrhizae. The individual and in mixture use of wild ectomycorrhizal fungi increased the morphological and biological quality of P. radiata; therefore, the application of these fungi is recommended for the production of seedlings in nurseries in Vilcashuaman and other high-Andean areas.